2019
DOI: 10.1111/1750-3841.14635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Freeze–Thaw Cycles on Biochemical and Physical Quality Changes of White Shrimp (Penaeus vannamei) Treated with Lysine and Sodium Bicarbonate

Abstract: Freezing and thawing occur during storage, transportation, and retail display, leading to deterioration of frozen shrimp. The objective of this research was to investigate the change in quality of frozen white shrimp treated by lysine and NaHCO3 after multiple freeze–thaw cycles. Shrimp were soaked in lysine and lysine/NaHCO3 each at 1% (w/v) frozen in an air‐blast freezer at −30 °C, and kept in a chest freezer (−18 ± 2 °C) for a week before they were thawed using tap water before the analysis (freeze–thaw cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…An extensive literature on mechanisms of lipid oxidation in frozen fish have accumulated till date (Ashton, 2002; Hematayar et al., 2019; Hyldig et al., 2012), with particular emphasis on optimizing animal welfare, preprocessing, packaging, and frozen storage temperature to avoid it (Ashton, 2002; Londahl & Nilsson, 2003; Secci & Parsi, 2016). Repeated freeze–thaw cycles can also accelerate lipid oxidation by fracturing the cell, promoting phospholipase and lipoxygenase enzymes (Wachirasiri et al., 2019).…”
Section: Results Of Literature Review and Metadata Analysesmentioning
confidence: 99%
“…An extensive literature on mechanisms of lipid oxidation in frozen fish have accumulated till date (Ashton, 2002; Hematayar et al., 2019; Hyldig et al., 2012), with particular emphasis on optimizing animal welfare, preprocessing, packaging, and frozen storage temperature to avoid it (Ashton, 2002; Londahl & Nilsson, 2003; Secci & Parsi, 2016). Repeated freeze–thaw cycles can also accelerate lipid oxidation by fracturing the cell, promoting phospholipase and lipoxygenase enzymes (Wachirasiri et al., 2019).…”
Section: Results Of Literature Review and Metadata Analysesmentioning
confidence: 99%
“…A TA‐XT plus texture analyzer (Stable Micro Systems Ltd, Godalming, UK) was used to measure the texture of fillet according to the method of Wachirasiri, Wanlapa, Uttapap, Puttanlek, and Rungsardthong () with slight modifications. Largemouth bass thawed fillets were cut into 2 × 2 × 2 cm 3 cubes and weighed about 7.5 ± 0.05 g. Texture profile analysis (TPA) mode of a texture analyzer and (P/50) stainless steel probe were used to analyze the texture properties of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, no significant difference was observed in the shear force of gelatin hydrolysate-and mixed phosphates-treated shrimp between freeze-thawing at 1 and 5 cycles (P > 0.05). Wachirasiri et al (2019) reported that untreated shrimp were tougher when subjected to a higher freeze-thaw cycle, and shrimp treated with lysine and lysine/NaHCO 3 could maintain cutting force throughout 5 freeze-thaw cycles. It indicates that gelatin hydrolysate may serve as a potential cryoprotectant in frozen shrimp, delaying the denaturation of muscle protein induced by recrystallization occurring from the freeze-thawed process.…”
Section: Resultsmentioning
confidence: 99%